Antiapoptotic Molecule Survivin in Transplantation: Helpful or Harmful? - Sara Assadiasl; Mohammad Javad Mousavi; Aliakbar Amirzargar (Journal of Transplantation)
Survivin, an antiapoptotic molecule from inhibitor of apoptosis protein (IAP) family, is most known for its implication in cancer as there are some efforts to apply it for diagnostic as well as therapeutic purposes in oncology. On the other hand, it could be a useful molecule to be positively targeted when trying to save tissue and promote cells viability. Since protecting the allograft from ischemia reperfusion injury and inflammation-induced damage is a considerable objective in transplantation, it is reasonable to take advantage from antiapoptotic agents like survivin in order to achieve this goal. However, survivin’s potential ability to induce malignancies makes some concerns about its use in clinic. The other barrier is this molecule’s involvement in lymphocytes development and proliferation which might increase the risk of graft rejection due to adaptive immune system overactivation. In this review we summarize the few studies carried out about survivin’s effect on graft survival and probable advantages and disadvantages of its overexpression in transplantation.